Advancing therapy with iGlarLixi versus premix BIAsp 30 in basal insulin‐treated type 2 diabetes: Design and baseline characteristics of the SoliMix randomized controlled trial. Issue 6 (29th April 2021) - McCrimmon, Rory J.; Al Sifri, Saud; Emral, Rifat; Mohan, Viswanathan; Sauque‐Reyna, Leobardo; Trescolí, Carlos; Lalic, Nebojsa; Alvarez, Agustina; Demil, Nacima; Coudert, Mathieu; Shaunik, Alka; Bonnemaire, Mireille; et al.
Abstract: Aim: Premix insulin is commonly used in some regions of the world, despite the higher risk of hypoglycaemia and weight gain compared with basal insulin, based on the premise that it offers a simplified insulin regimen. iGlarLixi is a once‐daily titratable fixed‐ratio formulation that combines basal insulin glargine 100 units/mL (iGlar) and the GLP‐1 RA, lixisenatide, which offers a single‐injection option for treatment intensification, with improved HbA1c reductions, similar hypoglycaemia risk and more favourable bodyweight profiles over iGlar alone. This randomized controlled study directly compares, for the first time, treatment intensification with iGlarLixi versus premix insulin analogue biphasic insulin aspart 30 (BIAsp 30) in adults with T2D inadequately controlled on basal insulin in combination with one or two oral antihyperglycaemic drugs. Materials and Methods: This was an open‐label, active‐controlled, comparative, parallel‐group, multicentre, phase 3b study. In total, 887 adults with T2D uncontrolled on basal insulin were randomized to switch to either iGlarLixi once daily, or BIAsp 30 twice daily, for 26 weeks. Results: Overall, 887 participants were enrolled (mean age 59.8 years, 50.2% female) from 89 centres in 17 countries. At baseline, 65.6% had a duration of T2D of 10 years or longer, and the mean HbA1c at baseline was 8.6%. Conclusions: The study directly compared the efficacy and safety of iGlarLixi versus BIAsp 30 in people with T2D uncontrolled on basal insulin and one or more oral antihyperglycaemic agents. These results provide robust clinical data that may inform clinicians in their therapeutic management of people with T2D uncontrolled on basal insulin requiring additional therapy.